2015
DOI: 10.1095/biolreprod.114.127027
|View full text |Cite
|
Sign up to set email alerts
|

MAPK3/1 (ERK1/2) and Myosin Light Chain Kinase in Mammalian Eggs Affect Myosin-II Function and Regulate the Metaphase II State in a Calcium- and Zinc-Dependent Manner1

Abstract: Vertebrate eggs are arrested at metaphase of meiosis II, a state classically known as cytostatic factor arrest. Maintenance of this arrest until the time of fertilization and then fertilization-induced exit from metaphase II are crucial for reproductive success. Another key aspect of this meiotic arrest and exit is regulation of the metaphase II spindle, which must be appropriately localized adjacent to the egg cortex during metaphase II and then progress into successful asymmetric cytokinesis to produce the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 101 publications
(184 reference statements)
0
8
4
Order By: Relevance
“…Intriguingly, we recently uncovered that the active myosin II ring is lost upon Cdc42 inactivation (Dehapiot et al, 2021). Therefore, while the current view is that the myosin II ring is driven by myosin light chain kinase/MLCK (Deng et al, 2005; Matson et al 2006; Deng et al, 2007; Ajduk et al, 2011; McGinnis et al, 2015; Mackenzie et al, 2016), our observations rather support a Cdc42-dependent mechanism. In line with this view, we previously reported that Cdc42-inhibited MII oocytes do not experience spindle drift, despite a loss of the actin cap (Dehapiot et al, 2013; Dehapiot and Halet, 2013).…”
Section: Introductioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Intriguingly, we recently uncovered that the active myosin II ring is lost upon Cdc42 inactivation (Dehapiot et al, 2021). Therefore, while the current view is that the myosin II ring is driven by myosin light chain kinase/MLCK (Deng et al, 2005; Matson et al 2006; Deng et al, 2007; Ajduk et al, 2011; McGinnis et al, 2015; Mackenzie et al, 2016), our observations rather support a Cdc42-dependent mechanism. In line with this view, we previously reported that Cdc42-inhibited MII oocytes do not experience spindle drift, despite a loss of the actin cap (Dehapiot et al, 2013; Dehapiot and Halet, 2013).…”
Section: Introductioncontrasting
confidence: 92%
“…These results are consistent with a loss of actomyosin contractility in the polarized cortex of MRCK-inhibited oocytes. Importantly, these data also demonstrate that inactivation of ring myosin II is not associated with a drift of the MII spindle away from the cortex, contrary to previous studies using ML-7 (Deng et al, 2005;Deng et al, 2007;McGinnis et al, 2015).…”
Section: Cdc42 Recruits Mrckβ To the Polarized Cortex For Myosin II A...contrasting
confidence: 78%
See 1 more Smart Citation
“…Because it took 1 h to set up imaging, the videos and quantifications represented the effect of 1-h pretreatment with each drug and 16-h migration in the presence of each drug. Phase-contrast imaging (McGinnis et al, 2015) was performed using an AxioObserver Z1 microscope equipped with an incubation chamber (37°C and 5% CO 2 ), a Zeiss EC Plan Neofluar 10×/0.3 Ph1 objective, and AxioVision software at 10-min intervals for 16 h. The migration area was calculated by subtracting the area measured at time 0 from the area measured after 16 h. PIV analysis of live-cell phase-contrast time-lapse videos was performed using MatLab as described (Weiger et al, 2013; Lee et al, 2016). Two interrogation window sizes (64 × 64 and 32 × 32 pixels) were used to segment the images.…”
Section: Methodsmentioning
confidence: 99%
“…If desired, oocytes can be loaded with DAPI to label the maternal DNA. Our method is based on what was originally reported for studies of sperm–egg fusion [32], incubating oocytes in culture medium containing 1 μg/mL DAPI for 90 min, followed by washing the oocytes through three drops of culture medium [33]. Alternatively oocytes can be microinjected with mRNA encoding a fluorescently tagged histone (e.g., H2B-mCherry [34, 35]).…”
Section: Methodsmentioning
confidence: 99%